2011
DOI: 10.1134/s1068162011030149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of cDNAs coding for a serine proteinase and a Kunitz-type inhibitor in the venom gland of the Vipera nikolskii viper

Abstract: Serine proteinases and Kunitz type inhibitors are widely represented in venoms of snakes from different genera. During the study of the venoms from snakes inhabiting Russia we have cloned cDNAs encoding new proteins belonging to these protein families. Thus, a new serine proteinase called nikobin was identified in the venom gland of Vipera nikolskii viper. By amino acid sequence deduced from the cDNA sequence, nikobin differs from serine proteinases identified in other snake species. Nikobin amino acid sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The data obtained in the present work are in good agreement with the published results; the basic and acidic PLA2 subunits forming heterodimeric enzymes account for more than 50% of the V. nikolskii venom ( Table 1 ). Earlier, cDNA encoding SP nikobin and Kunitz type inhibitor in the V. nikolskii venom gland was cloned and sequenced [ 11 ]. In this study we have found that nikobin is the main SP in the V. nikolskii venom (more than 12% of the total protein content, Table 1 ) and Kunitz-type serine protease inhibitor ki-VN was also the main protein of the Kunitz family in this venom (about 0.6%, Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained in the present work are in good agreement with the published results; the basic and acidic PLA2 subunits forming heterodimeric enzymes account for more than 50% of the V. nikolskii venom ( Table 1 ). Earlier, cDNA encoding SP nikobin and Kunitz type inhibitor in the V. nikolskii venom gland was cloned and sequenced [ 11 ]. In this study we have found that nikobin is the main SP in the V. nikolskii venom (more than 12% of the total protein content, Table 1 ) and Kunitz-type serine protease inhibitor ki-VN was also the main protein of the Kunitz family in this venom (about 0.6%, Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The isolated PLA2s were studied in more details and found to exert their action both on lipid membranes [ 8 ] and on nicotinic acetylcholine receptor [ 9 ]. The venom of Nikolsky’s viper was also partially characterized and several proteins including heterodimeric neurotoxic PLA2s were identified [ 10 , 11 ]. The venoms of other Russian viper species are characterized very poorly.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D structures of two classical members dendrotoxin‐K (DTX K) and dendrotoxin I (DTX I) have been determined, the molecular architectures of which are essentially identical to the structure of BPTI, a typical Kunitz‐type serine protease inhibitors without inhibitory activities for ion channels. Another kind of KTT from snake venom showed diverse proteases inhibitory activities, but lacked the ion channel investigation information, such as OH‐TCI , Pr‐mulgins , Bungaruskinin , Nikobin , PIVL and Textilinin‐1 . The aim of this study was to explore whether bifunctional KTT is present in snake venom.…”
Section: Introductionmentioning
confidence: 99%
“…Vaa SP-VX and Vaa SP-6 may thus be considered to be isoforms. Searching in the non-redundant NCBI database revealed another SVSP with a high sequence similarity to that of Vaa SP-VX, namely nikobin, from the venom of Vipera nikolskii [ 21 ]. The predicted amino acid sequence of the mature form of nikobin shared 97.42% identity with Vaa SP-6 and 97.00% with the sequenced parts of Vaa SP-VX ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%